Freedom, Entitlement, and the Path to Development - Chauffour, Jean-Pierre (World Bank, Washington, DC, 2012)
Twenty years after the revolutions of Central and Eastern Europe, the Arab Spring is again raising some fundamental questions about the place of freedom and entitlement in development. Depending on the balance between free choices and more coerced decisions, individual opportunities to learn, own, work, save, invest, trade, protect, and so forth could vary greatly across countries and over time. Reviewing the economic performance of more than 100 countries over the past 30 years, new empirical evidence tends to support the idea that economic freedom and civil and political liberties are the root causes of why certain countries achieve and sustain better economic outcomes. In contrast, entitlement rights do not seem to have any significant effects on long-term per capita income, except for a possible negative effect. These results tend to support earlier findings that, beyond core functions of government responsibility (including the protection of liberty itself), the expansion of the state to provide for various entitlements (including so-called economic, social, and cultural rights) may not make people richer in the long run; it may even make them poorer.